Compatibility of regional and multilateral trading agreements: reforming the WTO process - Sampson, Gary P. (American Economic Review, 1996)
While the pillar of the World Trade Organization' (WTO) with respect to trade in goods, services, and intellectual property is nondiscrimination, the cornerstone of trading is discrimination.2 There has been a proliferation of trading in recent years. Twenty-nine new have been notified to the General Agreement on Tariffs and Trade (GATT) and the WTO since 1992: 27 on merchandise trade and two on trade in services. This is almost half the number of still in existence and notified to GATT prior to 1992. All but three WTO members are parties to at least one agreement, and some are parties to many more. It is therefore not surprising that there is renewed interest in whether compete with, or complement, the multilateral trading system.4 While there may be no clear answer, it cannot be denied that recent developments have major implications for the rules-based multilateral trading system. One such development is that tariff preferences have or will become relatively unimportant in many trading agreements. The reasons for this include the high proportion of trade outside many preferential agreements, the limits to the coverage of the tariff preferences themselves, the high share of post-Uruguay Round tariffs that will be bound at zero, and the low level of most-favorednation (MFN) tariffs faced by non-preferencereceiving countries. This development is accompanied by the fact that the scope of application of many has extended well beyond tariff preferences to disciplines that were traditionally the domain of GATT or may in the future be dealt with by the WTO. The European Union (EU) provides a good example.' Despite the numerous countries receiving tariff preferences, its largest trading partners are outside the network of these agreements. In fact, 45 percent of EU imports originate in non-preference-receiving countries (e.g., 17 percent in the United States and 10 percent in Japan). While tariff preferences are of considerable potential importance, with the implementation of Uruguay Round commitments, 51 percent of the value of imports from non-preference-receiving countries will enter the EU under bound duty-free tariff rates. Further, the trade-weighted tariff average on manufactured imports from these countries will be 3.1 percent.6 * Development Division, World Trade Organization, Geneva, Switzerland. Helpful comments from Maria Pillinini of the WTO are gratefully acknowledged, as are those of Richard Snape of Monash University and Industries Commission, Australia. The views expressed in this article are those of the author and not the organization for which he works. 'The WTO came into existence on 1 January 1995 to, inter alia, facilitate the administration of the WTO that emerged from the Uruguay Round, one of which is the revised 1947 General Agreement on Tariffs and Trade (i.e., GATT 1994b). 2 Unless otherwise specified, the term regional trading agreements refers to both customs unions and free-trade areas for trade in goods. The extent of discrimination in is related to the ease of accession of non parties and the openness of the in general. 'The three are Japan, Korea, and Hong Kong. There were 128 Members of GATT, and following the completion of domestic ratification and WTO accession procedures, there will be approximately 160 members of the WTO in the next few years. There are presently 120 members. 4 There are many excellent contributions to this debate; see, for example, Richard Snape, et al. (1993), Jagdish Bhagwati (1995), and WTO (1995). 'Trade between the 15 members of the EU accounts for 60 percent of total EU trade. The EU offers contractual preferences to 26 countries under free-trade, association, or cooperation agreements, and to 70 countries under the Lom6 Convention. It offers noncontractual preferences to 145 countries under the Generalized System of Preferences (GSP). 6 While tariffs on agricultural products are generally higher than those on manufactured goods, the agricultural sector is typically dealt with outside EU preferential agreements.